Development Stages of Education in Foreign Countries (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article discusses one of today's most important issues, the countries of the world, the education system, their specific aspects, research methods, stages of development, and a number of scientific and practical tasks.